Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2015 - Yang, Gi-Chul; Ao, Sio-Iong; Huang, Xu; Castillo, Oscar (Springer Nature Singapore : Imprint: Springer, 2016)
This volume comprises selected extended papers written by prominent researchers participating in the International MultiConference of Engineers and Computer Scientists 2015, Hong Kong, 18-20 March 2015. The conference served as a platform for discussion of frontier topics in theoretical and applied engineering and computer science, and subjects covered include communications systems, control theory and automation, bioinformatics, artificial intelligence, data mining, engineering mathematics, scientific computing, engineering physics, electrical engineering, and industrial applications. The book describes the state-of-the-art in engineering technologies and computer science and its applications, and will serve as an excellent reference for industrial and academic researchers and graduate students working in these fields.